2002
DOI: 10.1046/j.1365-2362.2002.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols induce interleukin‐1β production in human macrophages

Abstract: Our results show that oxysterols, and 25-hydroxycholesterol in particular, may modulate the inflammatory response in human macrophages. Consequently the presence of oxysterols in atherosclerotic tissue may dramatically influence the effect of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 41 publications
(59 reference statements)
4
44
0
Order By: Relevance
“…Under in vivo conditions, the oxysterols are always present together with a very high excess of cholesterol, and this cholesterol may decrease or prevent the activity of the oxysterol ( 31 ). It has been reported that 25-hydroxycholesterol induces production of interleukin 1 ␤ and interleukin 8 from human macrophages ( 32,33 ). It cannot be excluded that a local interleukin release as a consequence of the high levels of 25-hydroxycholesterol may be of pathogenetic importance in the SPG5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Under in vivo conditions, the oxysterols are always present together with a very high excess of cholesterol, and this cholesterol may decrease or prevent the activity of the oxysterol ( 31 ). It has been reported that 25-hydroxycholesterol induces production of interleukin 1 ␤ and interleukin 8 from human macrophages ( 32,33 ). It cannot be excluded that a local interleukin release as a consequence of the high levels of 25-hydroxycholesterol may be of pathogenetic importance in the SPG5 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular accumulation of 7-ketocholesterol leads to increased production of reactive oxygen species and induces apoptosis in various cell types, including macrophages, endothelial cells, and smooth muscle cells (12)(13)(14)(15). In addition, oxysterols induce inflammatory gene expression in monocytemacrophages (34)(35)(36)(37). Therefore, 7-ketocholesterol and related oxysterols probably have an important role in the pathogenesis of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Paul et al showed that CRP is present in the human arterial intima of atherosclerotic lesions by histological examination 45) ; furthermore, Kobayashi et al reported that, using a sample from directional coronary atherectomy, the expression of CRP was colocalized with p22phox, and CRP directly induced p22phox expression, generating reactive oxygen species in cultured smooth muscle cells 46) . Therefore, CRP may promote the production of 7-KCHO in coronary artery plaques, consequently increasing s-7KCHO, however, some reports have indicated that oxysterol influences proinflammatory properties [47][48][49][50][51] . Joffre et al reported that 7KCHO enhanced interleukin-8 gene expression using porcine retinal pigment epithelial cells 51) .…”
Section: Relation Between Concentration Of S-7kcho and Inflammationmentioning
confidence: 99%